Crown structure indicates tree secondary growth, competition legacy, and growth potential of dominant species in Europe - Shamim Ahmed; Torben Hilmers; Enno Uhl; Frederico Tupinambá-Simões; Felipe Bravo; Miren del Río; Hans Pretzsch (Ecological Indicators)
Crown trait-based ecology has significantly advanced, yet a substantial knowledge gap remains regarding its predictive power on internal tree morphology and future growth potential across different species. Our research addressed this gap by examining how crown traits of various species manifest in temporal tree growth dynamics by answering three research questions (QⅠ): Are there general relationships between crown structure and secondary growth across species? (QⅡ) How do crown structure and secondary growth links vary among species and functional groups? (QⅢ) To what extent does a tree’s crown structure explain the variation in secondary growth over different periods?We conducted a comprehensive study to answer these questions, utilizing high-resolution 3D crown structure data from terrestrial laser scanning and growth ring data from tree coring. Our research explored the relationship between crown structure and growth rings in six dominant tree species in Europe (Picea abies (L.) H. Karst., Pinus sylvestris L., Pseudotsuga menziesii (Mirbel) Franco, Larix decidua Mill., Fagus sylvatica L., and Quercus robur L.) across Germany and Spain. These species, representing diverse functional identities, provide a comprehensive spectrum for analysis, ensuring the robustness of our findings.Our findings demonstrated a consistent link between crown structure (explained by projection area, crown length, ratio, slenderness, top-heaviness, etc.) and secondary growth, varying across species and functional identities. Coniferous species (e.g., P. abies, P. menziesii, L. decidua) generally exhibited stronger associations between crown structure and tree ring width than broadleaf; in contrast, P. sylvestris and Q. robur demonstrated weaker predictive relationships due to their lower crown plasticity and more episodic growth. The current crown structure was a reliable predictor of tree secondary growth over decadal scales. However, stronger relationships emerged when considering the entire tree ring series, suggesting a long-term morphological legacy effect of crown structure.These results show the importance of understanding how specific traits related to different tree species and their functional roles impact tree structure and growth. By better understanding how trees adapt (plasticity) and how their past growth affects future development (crown legacy), we can manage environmental challenges more effectively. Therefore, this knowledge is valuable for improving forest management practices and offers useful insights for professionals working in forestry.